A photopolymerized composite hydrogel and surgical implanting tool for a nucleus pulposus replacement. (May 2016) - Schmocker, Andreas; Khoushabi, Azadeh; Frauchiger, Daniela A.; Gantenbein, Benjamin; Schizas, Constantin; Moser, Christophe; Bourban, Pierre-Etienne; Pioletti, Dominique P.
Abstract: Nucleus pulposus replacements have been subjected to highly controversial discussions over the last 40 years. Their use has not yet resulted in a positive outcome to treat herniated disc or degenerated disc disease. The main reason is that not a single implant or tissue replacement was able to withstand the loads within an intervertebral disc. Here, we report on the development of a photo-polymerizable poly(ethylene glycol)dimethacrylate nano-fibrillated cellulose composite hydrogel which was tuned according to native tissue properties. Using a customized minimally-invasive medical device to inject and photopolymerize the hydrogel insitu, samples were implanted through an incision of 1 mm into an intervertebral disc of a bovine organ model to evaluate their long-term performance. When implanted into the bovine disc model, the composite hydrogel implant was able to significantly re-establish disc height after surgery (p < 0.0025). The height was maintained after 0.5 million loading cycles (p < 0.025). The mechanical resistance of the novel composite hydrogel material combined with the minimally invasive implantation procedure into a bovine disc resulted in a promising functional orthopedic implant for the replacement of the nucleus pulposus.